Peningkatan Kemampuan Membedakan Bahasa Baku dan Tidak Baku Berdasarkan EYD: - Khairunnisa, Riska; Fadhila, Puan; Budiman, Budiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Standard word in Indonesian are ones that adhere to established linguistic norms. Spelling, conventional grammar, and common dictionary words are only a few of the linguistic norms that can be found in standard words. The purpose of this study is to ascertain how pupils use common and uncommon words. This study employs a qualitative descriptive methodology. Students from the Department of Indonesian Language Education at The State Islamic University of North Sumatra served as the research participants. According to the study's findings, most students at The State Islamic University of North Sumatra's Department of Indonesian Language Education already grasp both standard and non-standard words, and very few do not. Keyword: Standard Word, Non- Standard Word, Students